Effect of motor intrusion on the aerodynamic performances and unsteady characteristics of internal flow of a volute-free centrifugal fan. (June 2023) - Qin, Hengjun; Wang, Zhengdao; He, Haijiang; Yang, Wenxia; Wang, Zhongxian; Zhu, Zuchao; Zhang, Wei
The volute-free centrifugal fans are widely used in air conditioning and ventilation applications due to their simple configuration and easy maintenance. The motor normally intrudes towards the fan interior from the rear disc to reduce the size and achieve better compatibility. The size and geometry of the motor affects the local flow field, which may have a serious impact on the aerodynamic performances of the fan. In this paper, we numerically investigated the effect of motor intrusion on the performances and internal flow characteristics of the volute-free centrifugal fan at different flow rates. The numerical results reveal that the internal flow field varies with the increasing of motor height at all flow rates. Under large flow rate, the height of motor has more obvious influence on the static pressure and static pressure efficiency of the fan; as the height of motor increases from 0 to 4 H /8, the two values decrease by 82.8% and 49.7%, respectively. The flow is more unstable which are manifested by the intensified velocity and pressure fluctuations. Therefore, the blocking effect of motor cannot be ignored and must be taken into account for the design the volute-free centrifugal fans.